Urban planning in a hygienist key - Petrocelli, Santiago Pablo (Universidad Nacional del Litoral, 2020)
In every urban planning process, a particular system of values, beliefs and actions underlies the ways of thinking and intervening in the city. The situation, which once again places the City of Buenos Aires in the focus of an epidemic, generates an opportunity for discussion and elaboration of new urban paradigms, for which the local experience of hygienist urban planning is a relevant contribution. In this sense, the objective of this work is to draw an overview of the problems and approaches that most permeated urban planning policies in the City of Buenos Aires in the late nineteenth and early twentieth centuries; in articulation with its socio-spatial configuration, the role of the State and the professionals of the city in the representation and reconfiguration of urban problems, interests and realities. At that time, hygienism crossed the argentine political imaginary, in which the idea that the order of space would become an order of society permeated, and that in de face of the epidemiological crisis, the liberal State should give way to an intervening State for the sanitation of the city. In agreement, the Municipality of Buenos Aires made multiple interventions, physical and regulatory.